2019
DOI: 10.2196/13885
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Prevention Mobile Apps: Descriptive Analysis of Apps from the Most Popular Virtual Stores

Abstract: Background Provision of follow-up and care during treatment of people with suicidal intentions is a challenge for health professionals and experts in information and communications technology (ICT). Therefore, health professionals and ICT experts are making efforts to carry out these activities in collaboration by using mobile apps as a technological resource. Objective This study aimed to descriptively analyze mobile apps aimed at suicide prevention an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…While specific AVMH resources related to suicide are fewer compared to those addressing mental health challenges such as low mood and anxiety [55], many resources address a broad range of mental health concerns that may underlie self-harm or suicidal ideation. Although a recent systematic review and meta-analysis concluded that internet-based interventions directly targeting suicidal ideation using cognitive behavioral therapy represent a promising means of providing low-threshold support to address suicidal ideation [56], researchers have suggested that AVMH resources may not represent the most appropriate form of mental health support for individuals with this experience given the severity of symptoms and degree of risk involved [57]. Despite relatively low uptake, use of mental health resources among individuals who reported self-harm or suicidal ideation was significantly higher compared to the general population, suggesting a desire for support seeking in this population.…”
Section: Principal Findingsmentioning
confidence: 99%
“…While specific AVMH resources related to suicide are fewer compared to those addressing mental health challenges such as low mood and anxiety [55], many resources address a broad range of mental health concerns that may underlie self-harm or suicidal ideation. Although a recent systematic review and meta-analysis concluded that internet-based interventions directly targeting suicidal ideation using cognitive behavioral therapy represent a promising means of providing low-threshold support to address suicidal ideation [56], researchers have suggested that AVMH resources may not represent the most appropriate form of mental health support for individuals with this experience given the severity of symptoms and degree of risk involved [57]. Despite relatively low uptake, use of mental health resources among individuals who reported self-harm or suicidal ideation was significantly higher compared to the general population, suggesting a desire for support seeking in this population.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The recent analysis of 20 mobile apps proposed for suicide prevention has revealed several technical and human aspects, which still need to be clearly defined. The analysis concluded that the design and development of apps aiming to prevent and monitor suicide behaviour should be strongly supported by qualified mental health professionals understanding the needs of people being in the critical situations ( Castillo-Sánchez et al, 2019 ). A promising approach has been described, applying both digital phenotyping and machine learning linked to Fitbit, Apple Health kit and Facebook.…”
Section: Suicidalitymentioning
confidence: 99%
“…Mobile apps may provide innovative, efficient, and cost-effective means for delivering suicide intervention strategies. Systematic reviews have identified between 14 and 49 suicide prevention apps available on Australian and American app markets that vary in terms of target users (mostly for at-risk user, some third party, and combined), or populations (broad community or specific groups, e.g., military or youth), as well as content, features and functions (Aguirre et al, 2013, Castillo-Sánchez et al, 2019, de la Torre et al, 2017, Larsen et al, 2016, Luxton et al, 2015, Martinengo et al, 2019. The following five principal features and functions were identified in Luxton and colleagues (2015) review of 14 apps: information about suicide prevention; connection to services and emergency crisis lines; safety planning and coping strategies; clinical assessment; and patient contact.…”
Section: Introductionmentioning
confidence: 99%